PT. Bank Tabungan Negara (Persero) Tbk Kantor Cabang Semarang) - Bagus Jarot Kurniawan; Sri Suryoko; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2016)
BTN is a State-Owned Enterprises, which has the function to distribute services from government mortgage subsidies. The development of the distribution of funds to the credit subsidy that are free competition. This type of research is explanatory research. In this study population size can not be determined by the researchers as limited to the level of confidentiality of company data for the samples taken by 100 respondents. Determination of the sample using accidental sampling technique. Data is collected by using a questionnaire. Data were analyzed using correlation analysis, simple regression, and multiple regression. This research concluded that: (a) the quality of service of Bank BTN Semarang Branch Office is well, the effect between service quality and credit decision-making was 0,58. (b) promotion of the Bank BTN is well, the effect between the promotion and decision making was 0.519. (c) the decision making customers of Bank BTN is high, the effect between service quality, promotion and decision making are strong 0.605. Quality service and promotion simultaneously effect on decisions making with a value Fcount 28.030. Suggestions can be submitted is corporate need to increase loan repayment care workers, and increase promotional activities in order to increase the maximum results.